Utilizing the linguistic landscapes for contextual language learning / Kamisah Ariffin ... [et al.] - Ariffin, Kamisah; De Mello, Geraldine; Husin, Misyana Susanti; Anuarudin, Shirin; Omar, Nurhidayatul Shima (UiTM Press, 2020)
The usual contexts of language learning are mainly limited to the classroom. There is a challenge to connect the contents of classroom lessons to the world outside the classroom. This mini project explores the potential of using the linguistic landscapes as a learning space for contextual language learning. Its objectives are to find an approach that can supplement formal learning as well as to provide meaningful and continuous learning for the students. In this project, students were asked to apply what they learned in the classroom in the real world context. The findings suggest that linguistic landscapes can serve as an authentic source of learning materials that positively facilitate learning. The project supports a positive learning experience through learner immersion, engagement and motivation.